Letters to Belvedere: participatory cinephilia in late Francoism. (3rd April 2022) - Buse, Peter; Triana-Toribio, Nuria
ABSTRACT: This paper examines the role of participatory cinephilia in the resistance to censorship near the end of the Franco regime in Spain (1968–1974). It takes as its case study the letters pages, or Consultorio, of "Mr Belvedere" in the commercial Barcelona-based film magazine Nuevo Fotogramas . Reconstructing as much as possible the identities and concerns of those who wrote to the magazine, the paper concentrates above all on the distinctive style and mode of address of "Mr Belvedere" and the relationship and community that he built up with suffering cinéfilos and cinéfagos deprived of films, in whole or in part, by the censor. The paper concludes that the Consultorio not only had a key function in the continued transmission of film knowledge under the dictatorship, but that Mr Belvedere's playful and ironic style was consistent with the overall disposition of Nuevo Fotogramas, whose deliberate frivolity was in itself a challenge to the regime's values and norms.